Emerging technologies for photovoltaic solar cell production: a review (Research, Society and Development, 2022)
Among the energy generated from renewable sources, the photovoltaic one stands out. This type of energy is becoming more attractive every day, since it has zero greenhouse gas emissions. In addition to having sunlight as its source, that is, an inexhaustible supply. From the above, in view of the importance of renewable energies and the recent rise of photovoltaic technologies, the objective of the present study is to explain, through an integrative literature review, the ascendancy to the application of emerging technologies for the production of photovoltaic solar cells. The review was carried out through searches of scientific technical documents available in databases such as Scielo, Scopus, ScienceDirect, Capes Periodicals and in scientific repositories. Photovoltaic energy converts solar energy into electrical energy and has proven to be a sustainable and practical solution to the challenge of meeting the growing global demand for energy. Silicon is the most widely disseminated material in photovoltaic technology and in the production of solar cells. Third or last generation cells are also called emerging technologies, since most are in the experimental phase, encompassing a variety of materials that are mostly organic. The search for new technologies and materials that can improve various aspects of photovoltaic cells and panels such as strength, durability and greater efficiency in energy conversion is a current demand.